The role of intelligence services in forming paramilitary formations - Alispahić, Bakir (Technium Social Sciences Journal, 2021)
Intelligence services, as an important segment of national security, have an unconventional but very successful approach to modern way of acting in solving state problems. As such, special and specialized services of intelligence agencies, using elements of violence in the form of violent groups and formations, influence interstate relations and positions of states and their governments on a hierarchical scale within the world - global order. Paramilitary formations, as an extended arm of the intelligence services, perform dirty and illegal jobs for the state and its elite, without the state fearing sanctions of international justice and retaliation. The role and influence of paramilitary formations on the creation of new borders, gaining resources and securing a political position, are irreplaceable in the modern age of global anarchy, when the state of antagonism among states is at its peak. Paramilitary formations, through their client of the intelligence service, directly serve the government that is waging the Special War as a means of reaching the desired - planned goal such as, for instance, resources, in an unjust and illegal way, at the cost of other people’s lives. By recognizing and documenting the activities of the Special War and the work of intelligence services, it is possible to create countermeasures (counter-intelligence protection) that would reduce the consequences, and the first step is to understand the relationship between intelligence and paramilitary formations that create crises using asymmetric and non-kinetic methods, locally as well as regionally and globally.